An Unusual Cardiac Manifestation in Autosomal Dominant Polycystic Kidney Disease - Fausta Catapano; Stefano Pancaldi; Carlo Pace Napoleone; Lucia Barbara De Sanctis; Gaetano Gargiulo; Giuseppe Emiliani; Antonio Santoro (Case Reports in Nephrology)
Autosomal dominant polycystic kidney disease is a common hereditary disorder characterized by renal and extrarenal, cystic and noncystic manifestations. Connective tissue defects, including cerebral aneurysm, meningeal diverticula, abdominal wall hernias, intestinal diverticula, and cardiac valvular abnormalities, are widely known manifestations. Instead intracardiac aneurysms have never been reported in adults with autosomal dominant polycystic kidney disease. We describe a 65-year-old patient with end-stage renal disease due to autosomal dominant polycystic kidney disease and an atrial septum aneurysm associated with platypnoea-orthodeoxia syndrome.